BODY CONDITION SCORE AS A MARKER OF MILK YIELD AND COMPOSITION IN DAIRY ANIMALS - A. Mushtaq; M. S. Qureshi; S. Khan; G. Habib; Z. A. Swati; S. U. Rahman (Journal of Animal and Plant Sciences, 2012)
Under tropical condition the BCS may influence the feed intake and metabolism leading to variation in economic parameters. This study investigated the BCS as a regulator of milk yield (MY) and composition (MC) in dairy animals. A total of 154 animals, comprising Azakheli (AZ) and Nili-Ravi (NR) buffaloes, Holstein Friesian (HF), Jersey (JC), Sahiwal (SW), Achai (AC) and crossbreds (XB) cattle and Beetal (BT) goats were selected from various public and private farms in NWF Province of Pakistan. MY and BCS were recorded weekly and milk samples were collected for analysis. The experiment continued for 6 months postpartum in buffaloes and cattle and three months in goats during the year 2008. Higher BCS was maintained by AZ, XB and HF, medium by NR and lowest by AC, SW, JC and BT. Highest yield was recorded with moderate BCS in buffaloes. BCS correlated positively with fat and protein and negatively with lactose contents. MY decreased while BCS increased with advancing lactation. MY and BCS correlated inversely. The negative relationship may be due to mobilization of body reserves, indicating their better genetic potential as dairy breeds. We suggest that dairy buffaloes perform well under the tropical conditions and BCS can be used as a marker for MY and quality.
Keywords: Dairy breeds; Buffalo; Sahiwal; Achai; Crossbred; Beetal; BCS; milk composition and yield